Flavonoid constituents of Dobera glabra leaves: amelioration impact against CCl4-induced changes in the genetic materials in male rats - Ahmed Elkhateeb; Rasha R. Abdel Latif; Mona M. Marzouk; Sameh R. Hussein; Mona E. S. Kassem; Wagdy K. B. Khalil; Mohamed A. El-Ansari (Taylor & Francis Group, 2017)
Context: Dobera glabra (Forssk.) Poir (Salvadoraceae) is a highly valued tree with diverse importance as special mineral sourced feed and a folkloric tool for forecasting droughts. However, there are no reports on its phytochemical and biological investigations. Objective: Phytochemical investigation of D. glabra leaves and its protective potential against CCl4 inducing changes in the genetic materials. Materials and methods: D. glabra extract, DGE (70% MeOH/H2O), was applied to polyamide column chromatography, eluting with MeOH/H2O of decreasing polarities, followed by preparative chromatographic tools, yielded seven compounds. Three DGE doses (50, 100 and 200 mg/kg bw/d) were administrated for 8 weeks intragastrically to male albino rats prior treated with CCl4 (0.5 mL/kg/bw). The reactive oxygen species (ROS) levels, expression changes of glutamate transporters (GLAST, GLT-1 and SNAT3) mRNA, DNA fragmentation and glutathione peroxidase (GPx) activity were investigated in the liver tissues of these rats. Results: Isorhamnetin-3-O-β-glucopyranoside-7-O-α-rhamnopyranoside, isorhamnetin-3-O-α-rhamnopyranoside-7-O-β-glucopyranoside, kaempferol-3,7-di-O-α-rhamnopyranoside, isorhamnetin-3-O-β-glucopyranoside, kaempferol-3-O-β-glucopyranoside, isorhamnetin and kaempferol were identified. DGE (200 mg/kg bw) + CCl4 exhibited the most significant reduction in ROS levels and DNA fragmentation with 251.3% and141% compared to 523.1% and 273.2% for CCl4, respectively. Additionally, it increased significantly the mRNA expression of GLAST, GLT-1 and SNAT3 to 2.16-, 1.72- and 2.09-fold, respectively. Also, GPx activity was increased to 4.8 U/mg protein/min compared to CCl4 (1.8 U/mg protein/min). Discussion and conclusion: Flavonoid constituents, antioxidant effect and genotoxic protection activity of D. glabra were first reported. DGE may be valuable in the treatment and hindrance of hepatic oxidative stress and genotoxicity.